Cantilever beam shape control with light activated polymers using hierarchical particle swarm optimizer - Zhao, Yu; Zheng, Shijie; Li, Zongjun (Mechanics of advanced materials and structures, 2021)
A shape control with light activated polymers (LAPs) is designed in present article. Under ultraviolet light irradiation, the structures of crosslink networks in LAPs alter. Such alterations lead to macroscopical deformation. On this basis, LAPs possess the potential to be actuators. For shape control, so many parameters of actuators could be optimized. A three-layer hierarchical particle swarm optimizer (HPSO) algorithm is proposed to search the appropriate group of LAPs numbers, locations and lengths. Numerical simulations (monotonic function shape control and non-monotonic function shape control) illustrate that HPSO is effective.